Socio-cultural tradition of the Rabha tribes of North Bengal, India : In relation to fisheries - Roy, Aparna; Sinha, Archana; Manna, Ranjan K.; Das, Basanta Kumar; Majumdar, Sucheta (Journal of the Inland Fisheries Society of India, 2019)
Socio-cultural aspects of Rabha tribes in Terai-Dooars region of West Bengal have been studied to document their traditional knowledge in relation tofisheries. Survey revealed that in addition to agriculture, 39% of the Rabhas especially mid-aged women are also engaged in fishing from the rivers andstreams. So, fishing is a secondary source or alternative source of livelihood for them. Their fish consumption pattern has been described. Five types of fishing gears and two types of plant piscicides commonly used by the Rabha community have been reported. A unique song sung during fishing dance has been recorded and described. Traditional knowledge associated with Rabhatribe is attempted to be documented and preserved in view of rapid social transformation of the community.Keywords Socio-cultural, Rabha, tribe, fisheries